Comparative Prayer Time Computation: Nailul Watar, Ephemeris, and Istiwa’ Method - M. Saifulloh; Ahmadi Syifaul Anam; Jundil Ikrom; Agus Solikin; Ahmad Adib Rofiuddin (Islamic Astronomy Department, Sharia and Law Faculty, 2026)
Investigates the accuracy and consistency of prayer time calculations from both classical Islamic texts and modern astronomical data. I used a qualitative-comparative field research design, with Nailul Watar by KH. Ahmad Asrori, as the primary classical source, and the 2022–2023 astronomical ephemeris data, calculated using Akh. Mukkaram's Astrology. I also included supporting references on Islamic astronomy and prayer times. To collect data, I documented and analyzed the two methods before empirically validating them. The results show that the Nailul Watar method provides highly accurate calculations of Zuhr and Asr prayer times, with discrepancies from the ephemeris results measured in seconds and never exceeding one minute, without needing additional safety margins. Validation using the Istiwa' stick confirmed that the method meets the fiqh standards commonly used by Indonesian scholars, although observations showed that shadows appeared slightly earlier than the calculated times. The study suggests that further research be conducted by combining computational modeling of both methods and incorporating shadow-length data to improve precision in future prayer time determinations.